Optimization of Congenital Hypothyroidism Screening (SHK) Actions in Newborns in the Perinatology Room - Lili Marliana; Felix Kasim; Okto Hebron Purba (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: Congenital Hypothyroidism (CH) is a thyroid dysfunction disorder present at birth. Congenital Hypothyroidism Screening (CHS) is performed a few days after birth to detect CH early and prevent negative impacts on the child's growth and development. However, the implementation of CHS in healthcare facilities often faces challenges.Objective: This study aims to describe and analyze the efforts to optimize the implementation of CHS for newborns in the perinatology room of RSUD dr. H. Kumpulan Pane, Tebing Tinggi City. Research Method: This descriptive qualitative study used snowball sampling technique to select informants. Data was collected through interviews and observations, with five main informants and fifteen additional informants. The research was conducted from January to March 2024. Results: The implementation of CHS at RSUD dr. H. Kumpulan Pane still faces several challenges, such as limited knowledge and skills of the staff, only one trained staff member, and ineffective communication. Additionally, the procurement of disposable medical supplies (BMHP) from the Tebing Tinggi City Health Office for 2024 is still unclear. Conclusion: The implementation of CHS at RSUD dr. H. Kumpulan Pane needs improvement, particularly in staff training, internal communication, and BMHP procurement. The Health Office is advised to enhance training, ensure BMHP procurement, and strengthen monitoring and cooperation with the hospital to make CHS more effective.